A Preliminary Investigation on the / Graphemic Oscillation in Latin Inscriptions From Rome: The Relationship Between Vowel Alternations, Lexical Stress and Syllabic Structure - Papini, Alessandro (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper is aimed at supplementing the results obtained in Papini 2019. In particular, I will consider the position of the investigated / and / graphemic oscillations with respect to both 1) lexical stress (distinguishing between misspellings occurring in stressed and unstressed position) and 2) syllabic structure (i.e., open vs closed syllables). The aim of the present paper is to verify whether the relationship between the investigated spelling variations and these two variables might be regarded as simply due to chance.